Application of Linear Model to Determine the Relationship of the Team Developmental Performance Metrics in CES - Carriaga, Davic O; Esmeria, Giselle Joy (RSF Conference Series: Business, Management and Social Sciences, 2022)
Technical support plays a vital role in modern businesses today. As most businesses rely on digital infrastructure, technical support provides solutions to customers’ issues and queries. It helps in the retention of customers. This paper aims to measure performance of technical support through the use of linear model applied to a BPO company. The results were further analyzed using the principal components analysis. The results show that the Technical Knowledge contributes to the model as the most significant factor with a value of 1.05. Next to it is the Support Citizenship which is at 0.95. Communication, was at 0.91 and Context Awareness at 0.76. At the very least, Diagnosis/Analysis was at 0.69.